1995
DOI: 10.1021/j100001a028
|View full text |Cite
|
Sign up to set email alerts
|

Tris(monochlorophenyl)- and Tris(dichlorophenyl)phosphines: Molecular Geometry, Anodic Behavior, and ESR Studies

Abstract: Tris(monochloropheny1)phosphines 1-3 and tris(2,6-dichlorophenyl)phosphine (4) were prepared. The X-ray structure of 4 was determined. Electrochemical oxidation of 1-4 showed a good correlation between anodic peak potentials and Hammett d parameters in homologous series of substituted triarylphosphines. The ESR spectrum of radical-cation 4'+ was composed of a large doublet with the highest known coupling constant for triarylphosphoniumyl radicals (Ap = 366 G at -30 "C).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 3 publications
0
21
0
Order By: Relevance
“…The phosphane 5b could be integrated into the isosteric series of triarylphosphanes bearing one or no methyl substituent on the ortho-position of each phenyl ring, for which, in our previous studies,we had found a linear correlation between E p and the ∑σ + Hammett parameter. 1,2,26 However, 5a could not be integrated in this correlation and the ortho-hydroxymethyl substituent appeared to have a dramatic influence on its anodic potential value.…”
Section: Resultsmentioning
confidence: 95%
“…The phosphane 5b could be integrated into the isosteric series of triarylphosphanes bearing one or no methyl substituent on the ortho-position of each phenyl ring, for which, in our previous studies,we had found a linear correlation between E p and the ∑σ + Hammett parameter. 1,2,26 However, 5a could not be integrated in this correlation and the ortho-hydroxymethyl substituent appeared to have a dramatic influence on its anodic potential value.…”
Section: Resultsmentioning
confidence: 95%
“…Another approach for assessing the nucleophilicity of the phosphines is to compare their HOMO energy, which was also assessed by DFT. 36,37 The nucleophilicity should increase with increasing -donor ability of the phosphines or, in other words, with increasing s-character of the orbital containing the lone pair, which should also be the HOMO of the molecule. A higher s-character of the HOMO, going in hand with a higher energy level of the HOMO, is thus indicative for a higher nucleophilicity.…”
Section: Resultsmentioning
confidence: 99%
“…Different methods have been reported to determine the electronic properties of phosphines. The σ-donor ability increases when the s-character of the lone pair of the phosphine decreases, which is associated with a higher energy level of the HOMO [ 47 , 48 ]. Thus, DFT studies have been performed in order to calculate the energy level of the HOMO of compound 1 and compare it with other triarylphosphines which were also calculated.…”
Section: Resultsmentioning
confidence: 99%